Method for constructing flexible interdigital supercapacitor by fluorine / chlorine doped porous graphene nanosheet aqueous solution
The ultra-stable, low-layer fluorine/chloro-doped porous graphene nanosheet aqueous solution was prepared through one-step graphite electrocorrosion technology, and a flexible interdigital supercapacitor was constructed, which solved the problems of graphene agglomeration and stacking in the prior art, and achieved high-performance, flexibility and cyclic stability supercapacitors.
Patent Information
- Application Number
- CN202410902321.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-06
- Publication Date
- 2025-03-25
AI Technical Summary
It is difficult to develop flexible interdigital supercapacitors with strong charge storage capabilities, good flexibility and excellent stability, especially in avoiding graphene agglomeration and stacking.
The ultra-stable, low-layer fluorine/chloro-doped porous graphene nanosheet aqueous solution was prepared by one-step graphite electrocorrosion technology, and graphene was filled with a reduced pressure filtration device to the hollow part of the metal template, transfer the electrode pattern to the polymer transparent film, and packaged it with a water system or ionic liquid gel electrolyte to construct a flexible interdigital supercapacitor.
The supercapacitor is continuously cycled by 500,000 revolutions at a current density of 0.2 mA cm-2, and the capacity retention rate is close to 100%. It has excellent cycling stability and bending resistance, avoiding the capacity attenuation problems caused by graphene agglomeration and stacking.
Smart Images

Figure CN119694801A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for constructing a high-performance flexible interdigital supercapacitor, and in particular to a method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution, belonging to the field of energy storage device preparation. Background Art
[0002] With the rapid development of electronic information and wearable smart devices, the requirements for the use of micro flexible electronic devices are getting higher and higher. Traditional sandwich microelectronic devices based on metal wires have shortcomings such as high cost and poor flexibility, while flexible interdigital supercapacitors have the advantages of easy integration, high cycle stability, and high safety, becoming one of the most promising micro energy storage devices. Developing electrode materials with strong charge storage capacity, good flexibility and excellent stability, and realizing the series-parallel combination of multiple interdigital electrodes on the same flexible film are of great practical significance for constructing flexible interdigital supercapacitors that are resistant to bending, have long cycle life and can flexibly adjust power.
[0003] Graphene has a two-dimensional planar structure, a high theoretical specific surface area, and excellent chemical stability. It is the most promising electrode material in the field of flexible micro-supercapacitors. The uniformity and stability of graphene dispersion in aqueous solution are crucial to the yield of flexible interdigitated electrodes. Avoiding the stacking and agglomeration of graphene during the service of the electrode is critical to improving the stability and service life of the device. The construction of graphene surface charge distribution, sheet thickness, and porous structure can improve the uniformity and stability of graphene dispersion in water, and eliminate the agglomeration and stacking of graphene during charge storage. Introducing highly electronegative halogen elements into graphene to form CX bonds can break the original six-membered ring structure of graphene to produce a large number of surface pits, pores, and defects, generate charge redistribution on the graphene surface, and significantly improve the wettability of graphene in water. Few-layer graphene nanosheets can improve their uniformity and stability in water, which is conducive to the construction of flexible interdigitated electrode patterns with stable performance. Therefore, a simple, safe and green method is used to prepare few-layer porous halogen-doped graphene nanosheets, and a simple and controllable technology is used to construct flexible interdigital supercapacitors with good mechanical properties and excellent stability, which has important practical significance for the large-scale application of flexible energy storage devices. Summary of the invention
[0004] The present invention provides a method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution.
[0005] The scheme of the present invention is: a method for constructing a high-performance flexible interdigital supercapacitor with an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution, using a one-step graphite electrocorrosion technology to prepare a few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution, using a vacuum filtration device to fill the graphene into the hollow part of the metal template, transferring the graphene electrode pattern in the hollow area to a polymer transparent film, applying an aqueous gel electrolyte or an ionic liquid gel electrolyte to the electrode pattern, solidifying and film encapsulating, and constructing a flexible interdigital supercapacitor. The flexible interdigital supercapacitor constructed with aqueous gel as the electrolyte has a high capacitance at 0.2 mA cm -2 It can cycle continuously for 500,000 times at the current density with a capacity retention rate of nearly 100% and almost no capacity loss. The electrode structure maintains the original layered structure and there is no capacity attenuation problem caused by graphene agglomeration and stacking. It has excellent cycle stability. The flexible interdigital supercapacitor can be bent at any angle with almost no capacity loss and a retention rate of about 100%. Single supercapacitors are combined in series and parallel to prepare integrated circuits, which can achieve flexible regulation of output power.
[0006] As a preferred technical solution, the concentration of the few-layer fluorine / chlorine doped porous graphene nanosheet aqueous solution is 0.01-2 mg / ml, and it can be placed for three months without coagulation, and has super stable characteristics.
[0007] As a preferred technical solution, the ultra-stable few-layer fluorine / chlorine doped porous graphene nanosheet aqueous solution is characterized in that the few-layer fluorine / chlorine doped porous graphene nanosheet is about two layers of graphite thick, has a highly transparent property, and the size of the pores is 0.1-8 nanometers.
[0008] As a preferred technical solution, the high-performance flexible energy storage device has an efficiency of 0.2 mA cm -2 Under the lowest current density, it can cycle continuously for 500,000 times with a capacity retention rate of nearly 100%. The graphene electrode structure still maintains its initial layered structure, and there is no capacity attenuation problem caused by graphene agglomeration and stacking.
[0009] As a preferred technical solution, it is characterized in that the constructed flexible energy storage device has a capacity retention rate of about 100% at any bending angle and has excellent bending resistance and mechanical flexibility.
[0010] As a preferred technical solution, the preparation of the ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution comprises the following steps: 1) In a mixed solution of ammonium fluoride and ammonium chloride in dilute sulfuric acid, apply a voltage of 5-15 V in a two-electrode system, with graphite raw material as the working electrode, apply the voltage for 10-15 minutes, and the reaction temperature is room temperature; 2) The deionized water in step 1) is filtered and washed under reduced pressure for 3-5 times, ultrasonicated at room temperature for 10-40 min, allowed to stand for 10-48 hours, and the upper layer solution is taken to obtain an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution.
[0011] As a preferred technical solution, the method of constructing a high-performance flexible interdigital supercapacitor with an aqueous solution of ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheets can control the shape, size, thickness and interdigital spacing of the pattern in the hollow area according to the metal hollow template, and can adjust the number and arrangement of series-parallel patterns to achieve linear growth of output power.
[0012] Advantages of the present invention: Through one-step graphite electrocorrosion technology, the simultaneous construction of few-layer graphene nanosheets, porous structures, rich step defects and fluorine / chlorine doping can be achieved in a simple two-electrode system. The entire preparation method is simple and green, without the use of high temperature, high pressure and expensive instruments.
[0013] The few-layer highly transparent nanosheet structure, abundant pores, a large number of step defects and surface charge changes caused by fluorine / chlorine doping increase the wettability of graphene in water, increase the interlayer spacing of graphene and the repulsive force between nanosheets, and make the graphene aqueous solution super stable. At the same time, it overcomes the problem of easy agglomeration and stacking of graphene nanosheets. The constructed flexible interdigitated supercapacitor exhibits super excellent cycle stability and bending resistance.
[0014] Few-layer fluorine / chlorine doped porous graphene nanosheets play a triple role as electrode material, conductive agent and binder in flexible electrodes, and can easily realize the effective integration of multiple interdigitated electrodes on the same flexible substrate. Due to the high repeatability of the preparation method and the high yield of the interdigitated electrodes, the output power can be flexibly controlled, which has broad application prospects in the field of integrated circuits.
[0015] Due to the adoption of the above technical scheme, a method for constructing a high-performance flexible interdigital supercapacitor with an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution is provided. The ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution is prepared by a one-step graphite electrocorrosion technology, and the ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution is filtered under reduced pressure to the hollow area of the metal template, and the graphene electrode pattern of the obtained hollow area is transferred to a polymer transparent substrate, and an aqueous or ionic liquid gel electrolyte is applied to the electrode pattern to make an integrated circuit with any combination of series and parallel connections. The present invention constructs a porous structure, step defects, surface charge redistribution and a highly transparent few-layer nanosheet structure by introducing carbon-halogen bonds, significantly enhancing the dispersion uniformity and stability of graphene in water, improving the cycle stability of the constructed electrode, avoiding the problem of agglomeration and stacking of graphene during long-term service, and the constructed flexible interdigital supercapacitor has very good mechanical flexibility. The entire preparation process is simple and repeatable, and there is no use of metal current collectors, conductive agents and polymer adhesives, and the effective integration of multiple interdigital electrodes can be easily achieved on a flexible substrate. Figure 1 This is a scanning electron microscope image of the fluorine / chlorine doped porous graphene nanosheets prepared by the present invention on a silicon wafer; Figure 2 A transmission electron microscope image of the fluorine / chlorine doped porous graphene nanosheet prepared by the present invention; Figure 3 This is a spherical aberration electron microscope image of the fluorine / chlorine doped porous graphene nanosheet prepared by the present invention; Figure 4 An atomic force microscope image of the fluorine / chlorine doped porous graphene nanosheet prepared by the present invention; Figure 5 The X-ray powder diffraction pattern of the fluorine / chlorine doped porous graphene nanosheet prepared by the present invention; Figure 6 X-ray photoelectron spectroscopy data of fluorine / chlorine doped porous graphene nanosheets prepared in the present invention, (a) F 1s and (b)Cl 2p ; Figure 7 The photographs of (a) an undoped graphene nanosheet aqueous solution prepared by the present invention after being placed for one month, and (b) a photograph of a fluorine / chlorine doped porous graphene nanosheet aqueous solution after being placed for three months; Figure 8 (a) Schematic diagram of the size of the metal template prepared in the present invention, and (b) a picture of the prepared flexible interdigital electrode; Fig. 9 The flexible interdigital supercapacitor constructed with fluorine / chlorine doped porous graphene nanosheets and using polyvinyl alcohol / sulfuric acid (PVA / H2SO4) as electrolyte prepared by the present invention has a high conductivity at 0.2 mA cm -2Capacity retention rate after 500,000 cycles at the current density; Fig.10 The flexible interdigital supercapacitor constructed with fluorine / chlorine doped porous graphene nanosheets prepared by the present invention and using polyvinyl alcohol / sulfuric acid as electrolyte has a high conductivity at 0.2 mA cm -2 Electrode cross-section diagram before (a) and after (b) 500,000 cycles at the current density. Fig.11 The bending pictures (a) of the flexible interdigital supercapacitor constructed with fluorine / chlorine-doped porous graphene nanosheets prepared by the present invention and using polyvinyl alcohol / sulfuric acid as electrolyte at different angles, (b) cyclic voltammetry curves at different angles, and (c) constant current charge-discharge curves; Fig.12 Prepared by the present invention. (a) Physical demonstration of 10 interdigital electrodes in series integrated with polyvinyl alcohol / sulfuric acid as electrolyte constructed by fluorine / chlorine doped porous graphene nanosheets, (b) Change of integrated circuit voltage with the number of series connections; Fig.13 (a) A physical demonstration of 10 interdigital electrodes in parallel integrated with polyvinyl alcohol / sulfuric acid as electrolytes constructed by fluorine / chlorine doped porous graphene nanosheets prepared by the present invention, and (b) the change of integrated circuit current with the number of series connections; Fig.14 (a) Cyclic voltammetry curve and (b) constant current charge-discharge curve of the ionic liquid gel electrolyte type flexible device prepared by the present invention; Fig.15 The following are photos of the single ionic liquid gel electrolyte-based flexible device prepared by the present invention lighting up light-emitting diodes of different colors. DETAILED DESCRIPTION
[0016] The present invention provides a method for constructing a high-performance flexible interdigital supercapacitor from an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution to solve the problems in the above-mentioned background technology.
[0017] The scheme of the present invention is: using a one-step graphite electrocorrosion technology to prepare a few-layer fluorine / chlorine doped porous graphene nanosheet aqueous solution, using a vacuum filtration device to fill the graphene into the hollow part of the metal template, transferring the graphene electrode pattern in the hollow area to a polymer transparent film, applying an aqueous gel electrolyte or an ionic liquid gel electrolyte to the electrode pattern, solidifying and film encapsulating, and constructing a flexible interdigital supercapacitor. The flexible supercapacitor constructed with aqueous gel as the electrolyte has a high conductivity at 0.2 mA cm -2It can cycle continuously for 500,000 times at the current density with a capacity retention rate of nearly 100%. The electrode structure maintains the original layered structure, and there is no capacity attenuation problem caused by graphene agglomeration and stacking. It has excellent cycle stability. The flexible interdigital supercapacitor can be bent at any angle with a capacity retention rate of about 100%. Single supercapacitors are combined in series and parallel to prepare integrated circuits, which can achieve flexible regulation of output power.
[0018] As a preferred technical solution, the concentration of the few-layer fluorine / chlorine doped porous graphene nanosheet aqueous solution is 0.01-2 mg / ml, and it can be placed for three months without coagulation, and has super stable characteristics.
[0019] As a preferred technical solution, the high-performance flexible interdigital supercapacitor has an operating temperature of 0.2 mA cm -2 Under the current density, it can be cycled continuously for 500,000 times, and the capacity retention rate is about 100%. The graphene electrode structure still retains the initial layered structure, and there is no capacity attenuation problem caused by graphene agglomeration and stacking.
[0020] As a preferred technical solution, it is characterized in that the constructed flexible interdigital supercapacitor has a capacity retention rate of about 100% at any bending angle and has excellent bending resistance and mechanical flexibility.
[0021] As a preferred technical solution, the preparation of the ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution comprises the following steps: 1) In a mixed solution of ammonium fluoride and ammonium chloride in dilute sulfuric acid, apply a voltage of 5-15 V in a two-electrode system, with graphite raw material as the working electrode, apply the voltage for 10-15 minutes, and the reaction temperature is room temperature; 2) The deionized water in step 1) is filtered and washed under reduced pressure for 3-5 times, ultrasonicated at room temperature for 10-40 min, allowed to stand for 10-48 hours, and the upper layer solution is taken to obtain an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution.
[0022] As a preferred technical solution, the ultra-stable few-layer fluorine / chlorine doped porous graphene nanosheet aqueous solution is characterized in that the few-layer fluorine / chlorine doped porous graphene nanosheet is about two layers of graphite thick, has a highly transparent property, and the size of the pores is 0.1-8 nanometers.
[0023] As a preferred technical solution, the method of constructing a high-performance flexible interdigitated supercapacitor with an aqueous solution of ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheets can control the shape, size, thickness and spacing of the hollow areas of the pattern according to the designed metal template, and can adjust the number and arrangement of series-parallel patterns to achieve linear growth of output power.
[0024] In order to make the technical means, creative features, objectives and effects achieved by the present invention easy to understand, the present invention is further described below in conjunction with specific embodiments. Example
[0025] 1. Prepare 0.1 mol / L sulfuric acid solution with 0.1 mol / L ammonium fluoride and 0.1 mol / L ammonium chloride as electrolyte, graphite sheet as working electrode, platinum sheet as counter electrode, apply 10 V voltage under DC voltage for 10 minutes, and the graphite sheet is completely peeled off; the obtained black dispersion is filtered and washed with deionized water under reduced pressure for 3 times, ultrasonicated at room temperature for 20 min, and allowed to stand for 24 hours. Take the upper solution to obtain an aqueous solution of ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheets, and take a small amount of the solution and drop it on a silicon wafer for structural characterization, such as Figure 1 As shown, the obtained graphene nanosheets have good dispersion on the silicon wafer, and the diameter of the nanosheets is about 5 microns. Through transmission electron microscopy characterization, it is found that the obtained graphene nanosheets have a highly transparent characteristic, such as Figure 2 As shown. After spherical aberration electron microscopy characterization, it was found that there were a large number of step defects and pores with a size of 0.5-5 nanometers on the graphene nanosheets, such as Figure 3 As shown. The obtained graphene nanosheet was characterized by atomic force microscopy and the thickness was only 1.1 nanometers, indicating that it is about the thickness of two layers, as shown Figure 4 As shown. X-ray powder diffraction characterization found that the diffraction peaks of fluorine / chlorine doped porous graphene nanosheets were significantly shifted to lower angles compared to pure graphite and undoped graphene nanosheets, indicating that a larger interlayer spacing was obtained after doping, such as Figure 5 As shown. X-ray photoelectron spectroscopy revealed that fluorine and chlorine were successfully doped into graphene to form carbon-fluorine bonds and carbon-chlorine bonds, as shown Figure 6 shown.
[0026] 2. Compared with the undoped sample, which is prone to coagulation, the aqueous solution of few-layer fluorine / chlorine doped porous graphene nanosheets remained in its original state after being placed for three months without any coagulation and separation. Figure 7 shown.
[0027] 3. Prepare metal hollow mask templates of different shapes and sizes by laser etching, spread the metal mask template on a filter membrane with a certain pore size, measure 5 ml of fluorine / chlorine-doped graphene aqueous solution, and use vacuum filtration to evenly precipitate graphene in the hollow area of the metal template; peel off the metal template from the filter membrane, and obtain a graphene pattern with a specific shape on the filter membrane, cover the filter membrane with the graphene pattern with a clean polyethylene terephthalate transparent film, apply a pressure of 0.1-0.6 MPa and maintain it at this pressure for 1 minute, transfer the graphene pattern to the polyethylene terephthalate substrate, and obtain a flexible interdigital electrode, such as Figure 8 As shown, the pattern shape, size, thickness and spacing of the hollow areas of the metal hollow template can be adjusted arbitrarily without short circuiting. Polyvinyl alcohol / sulfuric acid aqueous gel is used as the electrolyte, coated on the interdigital area of the electrode pattern, and encapsulated with a flexible film such as tape to produce a flexible interdigital supercapacitor.
[0028] 4. The obtained flexible interdigital supercapacitor was subjected to a cycle stability test, such as Fig. 9 As shown, at 0.2 mA cm -2 After 500,000 cycles at the same current density, the capacity retention rate was 101.4%, with no capacity loss. By observing the cross-sectional structure of the electrode before and after the cycle, the entire electrode structure still maintained its original layered pore structure after the cycle, and no agglomeration and stacking of graphene nanosheets occurred. Fig.10 shown.
[0029] 5. The obtained flexible interdigital supercapacitor was subjected to a bending resistance test. Compared with the case of no bending, the capacity retention rate was 100% under the bending conditions of 45, 90, 135 and 180 degrees, without any capacity loss, and had excellent bending resistance and mechanical flexibility. Fig.11 shown.
[0030] 6. Integrate different electrode patterns on the same polyethylene terephthalate substrate using a series connection method. Fig.12 The photo shows ten real-life supercapacitors connected in series without any metal wires, adhesives or conductive agents. The output voltage of a single supercapacitor is 0.8 V, which increases linearly with the number of supercapacitors connected in series, reaching 8 V for ten supercapacitors connected in series. Fig.13 The picture shows ten parallel connections without metal wires, adhesives or conductive agents. The output current increases linearly with the number of parallel connections. Example
[0031] 1. Using the same steps as described in Example 1, based on the aqueous solution of few-layer fluorine / chlorine-doped porous graphene nanosheets, 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) ionic liquid and poly (vinylidene fluoride-co-hexafluoropropylene) (PVDF-HFP) were used to prepare the gel electrolyte to construct an ion gel type flexible interdigital supercapacitor. Fig.14 The cyclic voltammetry curve and constant current charge-discharge curve are given. The output voltage of a single device can reach 3.5 V, which is much higher than the output voltage of the device constructed with aqueous gel electrolyte.
[0032] 2. A single flexible interdigital device based on ionic liquid can light up light-emitting diodes of various colors, further broadening the application scenarios of flexible interdigital supercapacitors, such as Fig.15 shown.
[0033] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution, characterized in that: A one-step graphite electrocorrosion technique was used to prepare a few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution. A vacuum filtration device was used to fill the graphene into the hollow part of the metal template. The graphene electrode pattern in the hollow area was transferred to a polymer transparent film. An aqueous gel electrolyte or an ionic liquid gel electrolyte was applied to the electrode pattern, solidified and film-encapsulated to construct a flexible interdigital supercapacitor. The flexible supercapacitor constructed with aqueous gel as the electrolyte has a high conductivity at 0.2 mA cm -2 It can cycle continuously for 500,000 times at the current density with a capacity retention rate of nearly 100%. The electrode structure maintains the original layered structure, and there is no capacity attenuation problem caused by graphene agglomeration and stacking. It has excellent cycle stability. The flexible interdigital supercapacitor can be bent at any angle with a capacity retention rate of about 100%. Single supercapacitors are combined in series and parallel to prepare integrated circuits, which can achieve flexible regulation of output power.
2. The method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution as claimed in claim 1, characterized in that: The concentration of the ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution is 0.01-2 mg / ml, and it can be placed for three months without coagulation, and has the characteristic of ultra-stability.
3. The method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution as claimed in claim 1, characterized in that: The ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet is approximately two layers of graphite thick, has a highly transparent property, and has pores with a size of 0.1-8 nanometers.
4. The method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution as claimed in claim 1, characterized in that: The high-performance flexible interdigital electrode supercapacitor has a high current density of 0.2 mA cm -2 Under the lowest current density, it can cycle continuously for 500,000 times with a capacity retention rate of nearly 100%. The graphene electrode structure still maintains its initial layered structure, and there is no capacity attenuation problem caused by graphene agglomeration and stacking.
5. The method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution as claimed in claim 1, characterized in that: The high-performance flexible interdigital supercapacitor has a capacity retention rate of about 100% at any bending angle and has excellent bending resistance and mechanical flexibility.
6. The method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution as claimed in claim 1, characterized in that: The preparation of the ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution comprises the following steps: 1) In a mixed solution of ammonium fluoride and ammonium chloride in dilute sulfuric acid, apply a voltage of 5-15 V in a two-electrode system, with graphite raw material as the working electrode, apply the voltage for 10-15 minutes, and the reaction temperature is room temperature; 2) The deionized water in step 1) is filtered and washed under reduced pressure for 3-5 times, ultrasonicated at room temperature for 10-40 min, allowed to stand for 10-48 hours, and the upper layer solution is taken to obtain an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution.
7. The method for constructing a high-performance flexible interdigital supercapacitor using an ultra-stable few-layer fluorine / chlorine-doped porous graphene nanosheet aqueous solution as claimed in claim 1, characterized in that: The method for constructing a high-performance flexible interdigital supercapacitor can control the shape, size, thickness and spacing of the hollow areas of the pattern according to the metal hollow template, and can adjust the number and arrangement of series-parallel patterns to achieve linear growth of output power.